Auditor Reflections on Reimagining Accounting Curriculum: A Journey toward Ethics, Sustainability, and Transformative Learning - Wulandari, Putu Prima (UNHI Press, 2025)
This research is an imaginary dialogue between two auditors who have different professional backgrounds. The first auditor comes from a practitioner environment, while the second auditor has a background as curriculum and academic staff of a study program. The two of them discuss about the accounting education curriculum, which is still overshadowed by economic rationalism and focusing on pragmatic competencies. Through this imaginary dialogue, the two of them initiate a concept regarding accounting education and fill the gap between accounting education and sustainability issues. The two auditors, through deconstruction process in the imaginary dialogue, reconfigure the meaning of accounting education producing a learning concept, namely transformative learning, which is supported by a cognitive dissonance strategy as an effort to sharpen the awareness of accounting graduates in the learning process. The collaboration of the two strategies is implemented in a harmony of accounting education intended for its graduates to be able to achieve the expected competencies, which include critical thinking skills, increased moral consciousness as accountants, increased awareness of the importance of professional accountant identity, and sustainability perspective possession.